Pulmonary Arterial Enlargement is Associated With Acute Chest Pain in Patients Without Obstructive Coronary Artery Disease. Issue 12 (9th February 2018) - Madam, Narasa; Mosleh, Wassim; Punnanithinont, Natdanai; Carmona-Rubio, Andres; Said, Zaid H; Sharma, Umesh C
Background: Pulmonary hypertension (PH) is an underdiagnosed cause for chest pain in patients without significant coronary artery disease (CAD). Studies showed that enlarged pulmonary arterial (PA) and right ventricular chamber sizes correlate with the severity of PH. Therefore, we studied the association between chest pain, right ventricular dimensions (RVDs), and PA size on coronary coronary tomographic angiography (CCTA). Methods: The CCTA of 87 patients presenting with chest pain without evidence of obstructive CAD was examined. The PA diameter (PAD), right atrial dimension (RAD), and RVD were measured. A comparative control cohort included 31 patients who presented without cardiopulmonary complaints and underwent thoracic CT. The risk for obstructive sleep apnea (OSA) was assessed using STOP-BANG questionnaires. Results: Patients with chest pain without obstructive CAD showed markedly dilated right atrial and ventricular chambers compared with standard parameters (right atrium: 48 ± 6.4 mm; right ventricle long axis: 61 ± 9.5 mm). When comparing chest pain vs non-chest pain group, respectively, the mean PAD measured 25.92 ± 0.43 mm vs 22.89 ± 0.38 mm ( P < .001), RAD2 measured 40.1423 ± 0.7108 mm vs 34.8800 ± 1.0245 mm ( P = .0048), and RVD2 measured 31.7729 ± 0.7299 mm vs 27.6379 ± 1.6178 mm ( P = .034). Chest pain was associated with higher PAD (odds ratio [OR]: 11.11, P < .05) after adjusting for age, sex, body mass index, history of hypertension, hyperlipidemia, congestive heart failure, chronic obstructive pulmonary disease, OSA, and smoking. The chest pain group had a mean STOP-BANG score of 3.9 ± 1.8 in all patients, and 3.62 ± 0.20 in patients without known history of OSA, representing an elevated risk index for the disease. Conclusions: In patients presenting with chest pain without obstructive CAD on CCTA, there is a strong association between the presence of chest pain and enlarged PAD. They also represent a high-risk group for OSA.